Caranan fibers (Mauritiella armata) and new reinforcements of polyester composites with natural fibers functionalized with graphene oxide and their application potential - Luciano Monteiro Almeida; Alisson Clay Rios da Silva; Felipe Perissé Duarte Lopes; Noan Tonini Simonassi; Sérgio Neves Monteiro; Verônica Scarpini Candido (Journal of Materials Research and Technology)
In the Amazon region, the choice and study of caranan fiber (Mauritiella armata) is justified by its potential being scarcely investigated and explored. This work aims to characterize the tensile mechanical properties, to evaluate their chemical compositions via Fourier Transform Infrared Spectroscopy (FTIR) and Raman Spectroscopy, as well as the morphologies via Scanning Electron Microscopy (SEM) of the composites with the incorporation of 0, 10, 20, and 30 vol% of non-functionalized and 0.5%p/v functionalized caranan fibers. For tensile properties, the composites showed decreases of 9.68% and 10.62% for the composites with 10 and 30 vol% of functionalized fibers, respectively, compared to the pure matrix, and an increase of 7.41% for the composite with 20 vol% of functionalized fibers. The flexural properties showed an increase with the incorporation of 10 vol% of functionalized caranan fibers compared to the pure polyester matrix. The impact test provided an increase of 169.88% for the composites with 30 vol% by volume of natural fibers and 152% for those with 30 vol% of fibers functionalized with graphene oxide compared to the pure polyester matrix. FTIR showed the presence of specific functional groups for the pure polyester matrix, graphene oxide, and with the addition of functionalized fibers for the composites. For the evaluation of Raman spectroscopy after the functionalization process, the presence of the D, G, and 2D bands was evident. The SEM indicated the main failure mechanisms that led the composite to fracture: porosities, river marks, fiber pull-out.